Treatment of textile wastewater with peat soil based system / A.B.M. Helal Uddin and Mohd Asri Mohd Nawi - Helal Uddin, A.B.M; Mohd Nawi, Mohd Asri (2006)
Peat soil is an organic soil formed from the compilation and degradation of residual plant materials over the years. Malaysian peal soil classified as tropical peat soil was successfully modified to work as a coagulant material. This Peat Coagulani (PC) was found effective for the clarification (if turbidity as well as colour from aqueous solutions It could effectively remove over 95% of the colour from standard dye solutions. It was also found that it could remove colour from textile waste water above 87% without any pH adjustment and at pH 5 it showed 94% colour removal from the textile waste water. The colour removal percentage of PC was higher compared to alum and poly aluminium chloride (PAC) which are 51% and 54% respectively at their optimum pH. PC treated textile waste water was further passed through a peat soil based jilter prepared from heat treated peat soil for the removal of chemical oxygen demand (COD). Laboratory scale study showed that this filter was able to remove above 90% of the remaining COD from the textile waste water.